PENERAPAN PEMBELAJARAN BERBASIS PROYEK TERHADAP BERPIKIR KREATIF SISWA KELAS V PADA MATERI SIKLUS AIR - Cahyaningsih, Ratna Dila; Sujana, Atep; Gusrayani, Diah (Jurnal Pena Ilmiah, 2019)
Sains learning is one of the processes in the formation of student behavior that leads the students to be competent in solving problems in a scientific process. Therefore, students must have creative thinking skills. However, student's creative thinking skills are still relatively low, so that project based learning is used. The purpose of this research is to know implementation of project based learning to creative thinking skills. The reserch design is quasi experiment by using nonequivalent control group design. The population in this research is all of students in grade V on all of Kramatmulya subdistrict. The sampling skills in this research is using purposive sampling technique with SDN II Ragawacana as experimental class and SDN Pajambon as control class. The instrument in this research is using tests in the form of tests of creative thinking skills and non tests in the form of observation of teacher performance, observation of student activities and field notes. Based on the results of the reserch can be know that project based learning has a positive effect on improving student's creative thinking skills significantly, with an average gain of 0,329. While in conventional learning, an average gain of 0,150. So that, the project based learning is better than conventional learning in improving student's creative thinking skills.